Structure and Development of the Gametophytes of Philippine Cheilanthoid Ferns, III. Cheilanthes concolor (Langsdorff et Fischer) R. Tryon - Zamora, Prescillano; Chaimongkol, S.; Marzan, M. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 5 No 2 (1993), 2007)
The gametophytes of Cheilanthes concolor (Langsdorff et Fischer) R. Tryon from the Philippines (Quezon City) are no different in pattern of development and in morphology from those from India with one possible notable difference, which is, that the gametophytes under report (which were grown from spores produced from 32-sporate sporangia) are apogamous while those from India (sporangial type of source was not stated) are sexual.